Vascular flora of La Puebla de Cazalla (Seville, Spain): taxa of chorological interest for the province of Seville - Pulgar, Íñigo; Herrera, José Manuel (Botanica Complutensis, 2017)
the province of Seville. The presence of taxa in no more than 3 squares of 10 x 10 km in the ANTHOS database and distribution of natural regions of western Andalucia are established as a criterion of rarity. The provincial locations of the selected taxa are reviewed.
Keywords: vascular plants; chorology; Campiña Alta.